2023
DOI: 10.1159/000531431
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Iron Restriction Protects against Aneurysm Rupture in a Mouse Model of Intracranial Aneurysm

Abstract: <b><i>Introduction:</i></b> Iron accumulation in vessel walls induces oxidative stress and inflammation, which can cause cerebrovascular damage, vascular wall degeneration, and intracranial aneurysmal formation, growth, and rupture. Subarachnoid hemorrhage from intracranial aneurysm rupture results in significant morbidity and mortality. This study used a mouse model of intracranial aneurysm to evaluate the effect of dietary iron restriction on aneurysm formation and rupture. <b>&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The MSR1 named CD204, was primarily found on the various types of macrophage surface and was responsible for the pro-inflammatory polarization both in vivo and in vitro ( 37 , 38 ). In the aspect of nutrition improvement, recent studies demonstrated that iron limitation and coenzyme Q10 (CoQ10) administration significantly ameliorated the macrophages infiltration and oxidative stress, thereby attenuating IA progression and rupture ( 39 , 40 ). Through engulfed ultrasmall superparamagnetic iron oxide particle, the macrophages enrichment vessel wall imaging in IA has potential in qualitative evaluation and can be used to evaluate the efficacy of medication ( 41 ).…”
Section: Macrophages Recruitment and Activation In Iamentioning
confidence: 99%
“…The MSR1 named CD204, was primarily found on the various types of macrophage surface and was responsible for the pro-inflammatory polarization both in vivo and in vitro ( 37 , 38 ). In the aspect of nutrition improvement, recent studies demonstrated that iron limitation and coenzyme Q10 (CoQ10) administration significantly ameliorated the macrophages infiltration and oxidative stress, thereby attenuating IA progression and rupture ( 39 , 40 ). Through engulfed ultrasmall superparamagnetic iron oxide particle, the macrophages enrichment vessel wall imaging in IA has potential in qualitative evaluation and can be used to evaluate the efficacy of medication ( 41 ).…”
Section: Macrophages Recruitment and Activation In Iamentioning
confidence: 99%